Dinamika Kewarisan Islam: Telaah Problematika Waris Mafqud (Orang Hilang), Mati Bersama, Khuntsa’ (Banci) dan Proses Penyelesaian Warisan - Rohman, Moh. Mujibur (ASASI: Journal of Islamic Family Law, 2023)
Inheritance is the assets left behind by someone who dies and has taken care of maintenance costs, paid off debts, and executed a will. Inheritance law has a very important position in Islam. The distribution of inheritance in Islam is something that must be resolved. Because, it is a gift from someone who has died. Distribution of inheritance according to Islamic law is declared to exist if the conditions for inheritance have been fulfilled by both the heir and the heirs. Among the conditions for dividing inheritance, namely, the death of the muwarits, the life of the heirs, and no obstacles to inheritance. However, problems arise if the distribution of inheritance does not fulfill one of the conditions for both the heir and the heirs themselves. As in certain cases, for example cases of mafqud (missing person), khuntsa' (sissy), and simultaneous death. So this research aims to find out how to resolve inheritance distribution where the conditions for inheritance distribution are not met. So to answer this question, the author uses a library research approach, namely research by searching for documents or literature based on books, journals, theses and others. The writing method uses normative juridical in its presentation. The results of this article show that the division of inheritance in certain cases can be resolved by knowing the legal status first to determine the size of the share that will be received by the heirs. The most important role in determining this legal status is the ijtihad of the judges.